Effects of radiation and chemical reaction on MHD flow past a vertical plate with variable temperature and mass diffusion - Rajput, U S; Kumar, Gaurav (Journal of Naval Architecture and Marine Engineering, 2019)
This research investigates the effects of radiation, chemical reaction and porosity of the medium on unsteady flow of a viscous, incompressible and electrically conducting fluid past an exponentially accelerated vertical plate with variable wall temperature and mass diffusion in the presence of transversely applied uniform magnetic field. The plate temperature and the concentration level near the plate increase linearly with time. The fluid model under consideration has been solved by Laplace transform technique. The model contains equations of motion, diffusion equation and equation of energy. To analyze the solution of the model, reasonable sets of the values of the parameters have been considered. The numerical data obtained is discussed with the help of graphs and tables. The numerical values obtained for skin-friction, Sherwood number and Nusselt number have been tabulated. It is found that the velocity of fluid increases when the values of permeability parameter, acceleration parameter and radiation parameter are increased. But trend is reversed with the chemical reaction parameter. It means that the velocity decreases when the chemical reaction parameter is increased.